Evaluation of Melongosides as Potential Inhibitors of NS2B-NS3 Activator-Protease of Dengue Virus (Serotype 2) by Using Molecular Docking and Dynamics Simulation Approach. (23rd August 2022) - Biswas, Partha; Hany Rumi, Ommay; Ahmed Khan, Dhrubo; Ahmed, Md Nasir; Nahar, Nusratun; Jahan, Rownak; Hasan Zilani, Md Nazmul; Paul, Tridib K; Hasan, Anamul; Bondhon, Tohmina Afroze; Jannat, Khoshnur; Hasan, Md Nazmul; et al.
Abstract : Dengue is a Flavivirus infection transmitted through mosquitoes of the Aedes genus, which is known to occur in over 100 countries of the world. Dengue has no available drugs for treatment; CYD-TDV is the only vaccine thus far approved for use by a few countries in the world. In the absence of drugs and a widely approved vaccine, attention has been focused on plant-derived compounds to the discovery of a potential therapeutic for DENV. The present study aimed to determine, in silico, the binding energies of the steroidal saponins, melongosides, to NS2B-NS3 activator protease of DENV-2, which plays an essential role in the viral replication. The blind molecular docking studies carried out gave binding energies (ΔG = −kcal/mol) of melongosides B, F, G, H, N, O, and P as 7.7, 8.2, 7.6, 7.8, 8.3, 8.0, and 8.0, respectively. All the melongosides interacted with the NS3 protease part of NS2B-NS3. Melongosides B, F, and N showed interactions with His51, while melongoside G interacted with Asp75 of NS3, to be noted, these are important amino acid residues in the catalytic site of the NS3 protease. However, the 200 ns molecular dynamic simulation experiment indicates significant stability of the protein-ligand interactions with the RMSD values of 2.5 Å, thus suggesting a better docking position and no disruption of the protein-ligand structure. Taken together, melongosides need further attention for more scientific studies as a DENV inhibitory agent, which if proven, in vivo and in clinical trials, can be a useful therapeutic agent against at least DENV-2.